Os sentidos e significados constituídos por adolescentes sobre os saberes escolares - Pinto, Aline Coralim Azevedo (2014)
The objective of this research was to understand the senses and the meanings constituted by adolescents about school knowledge, i.e., on the knowledge divulged in schools. The lack of scientific knowledge on this topic prevents or hinders the understanding on the students point of view of in relation to school's knowledge. The study is qualitative in nature and followed the socio-historical theory s assumptions. Two teenagers participated in it: a 12-year-old boy and a 14-years old girl, both without lag age/grade, enrolled in the final years of basic education in public schools. The two of them were linked to a Center for Children and Adolescents (CCA), situated in the west area of the city of São Paulo, in which they were contacted. Both agreed to participate in individual interviews, in which it was sought to obtain, in addition to personal data, their lives history, their experiences in school and the relationship they maintained with this institution and its knowledge. For data analysis, it was followed the instructions for constructing signification nuclei. Each of them were initially examined and subsequently articulated, in an internúcleos analysis, uncovering the particularities constituted by each subject. The similar or recurring aspects found in the subjects reports allowed identifying that school knowledge is simply instrumental for ascending social and financially. This seems to be a widespread vision of knowledge learned at school, since it is in accordance with the lessons taught both in families and schools. In fact, teachers preach school attendance as central to make this desire to happen. Clearly, the value of learning for the individuals is not explained, reason by which on the surface, at the level of meaning, the answer given by the students was just a mechanical reproduction of something learned long time ago: school knowledge is necessary for attaining a better material life, which is part of the truth but not the whole truth. Under these conditions, the passage by the school seems to serve exclusively to the future, having little relevance for the present time. The conclusion emphasized the need of making school a pleasant and living space by providing a more democratic and interesting education, paving the way for school knowledge be also enjoyed at the here and now